Global analysis of advanced/metastatic breast cancer: Decade report (2005–2015). (June 2018) - Cardoso, Fatima; Spence, Danielle; Mertz, Shirley; Corneliussen-James, Dian; Sabelko, Kimberly; Gralow, Julie; Cardoso, Maria-João; Peccatori, Fedro; Paonessa, Diego; Benares, Ann; Sakurai, Naomi; Beishon, Marc; et al.
Abstract: Approximately 0.5 million people worldwide die from metastatic breast cancer (mBC) every year. This manuscript provides an overview on the status of mBC in several regions of the world, highlighting the gaps in care, resources, and support available for patients with mBC. Primary research was conducted in 2015 and 2016, comprising four global qualitative and quantitative surveys of approximately 15, 000 individuals in 34 countries. Secondary research was conducted using literature reviews of peer-reviewed publications, patient survey reports, and media or online articles. There have been modest improvements in mBC outcomes over the past decade. Patients are not provided with adequate information about mBC. There is a need for open discussion with patients and caregivers about realistic goals; however, physicians are not trained in communicating with patients about their disease. Maintaining patients' quality of life is a crucial goal; however, this has not improved, and in some cases, may have declined in the past decade. Public awareness and understanding of mBC is limited, with damaging consequences for patients and caregivers. Issues affecting employment remain relevant to patients with mBC and their caregivers. Globally, mBC is associated with a substantial economic burden. Relationships with caregivers are crucial to patients with mBC, and caregiver support needs are often overlooked. A strong and united global effort among healthcare professionals, including clinicians, oncologists, pharmaceutical manufacturers, payers, and policy makers, and with advocates, families, and patients, is necessary to improve the outcome and quality of life for patients with mBC.